2020
DOI: 10.18231/j.ijced.2020.047
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of efficacy and safety of terbinafine and itraconazole in the management of tinea corporis et cruris

Abstract: The management of dermatophytosis is challenging in India and there are reports of using systemic antifungals at higher doses. But there are multiple reports of increased treatment failures with terbinafine at standard dosage as well, hence we conducted this study to compare efficacy and safety of high dose of terbinafine with itraconazole at standard dose. Topical ciclopirox olamine was used in both arms.This was randomized, open label, comparative study where 80 patients with tinea corporis et cruris infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In this study, itraconazole and terbinafine achieved comparable cure rates when used alone and achieved less non significant cure rates to the itraconazole + terbinafine combination. This was comparable to Shah et al who reported significant comparable cure rates of itraconazole and terbinafine when used alone 11 . Singh et al reported itraconazole to be more effective when compared to terbinafine 7 .…”
Section: Discussionsupporting
confidence: 85%
“…In this study, itraconazole and terbinafine achieved comparable cure rates when used alone and achieved less non significant cure rates to the itraconazole + terbinafine combination. This was comparable to Shah et al who reported significant comparable cure rates of itraconazole and terbinafine when used alone 11 . Singh et al reported itraconazole to be more effective when compared to terbinafine 7 .…”
Section: Discussionsupporting
confidence: 85%
“…[ 19 , 20 ] There are several research articles available that show the benefits of combination therapy. [ 21 - 27 ] However, there is no clarity for using medications from the same or other classes as those described above. Though some reviews advocate combining two separate classes of medicines, synergistic benefits of luliconazole and itraconazole have been demonstrated in a recent paper.…”
Section: Discussionmentioning
confidence: 99%